2022
DOI: 10.1001/jamacardio.2022.0480
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 15-mg Edoxaban on Clinical Outcomes in 3 Age Strata in Older Patients With Atrial Fibrillation

Abstract: This randomized clinical trial investigates the effect of 15-mg edoxaban in patients aged 80 years and older who are not candidates for standard-dose oral anticoagulants owing to bleeding risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“… 4 In addition, subgroup analyses of ELDERCARE‐AF confirmed the consistent benefit of edoxaban 15 mg irrespective of age (80–84 years, 85–89 years, and ≥90 years) and renal function (creatinine clearance 15–<30 mL/min, 30–50 mL/min, and >50 mL/min). 5 , 6 …”
mentioning
confidence: 99%
“… 4 In addition, subgroup analyses of ELDERCARE‐AF confirmed the consistent benefit of edoxaban 15 mg irrespective of age (80–84 years, 85–89 years, and ≥90 years) and renal function (creatinine clearance 15–<30 mL/min, 30–50 mL/min, and >50 mL/min). 5 , 6 …”
mentioning
confidence: 99%
“…Kuroda et al examined the effects of very low-dose edoxaban (15 mg) vs placebo across 3 age strata (80-84 years, 85-89 years, and ≥90 years) among Japanese patients with atrial fibrillation enrolled in the Edoxaban Low-Dose for Elder Care Atrial Fibrillation Patients (ELDERCARE–AF) trial. In this prespecified substudy of patients who were not considered candidates for standard doses of oral anticoagulants, the authors demonstrated that a once-daily 15-mg dose of edoxaban was superior to placebo in preventing stroke or systemic embolism across all 3 age strata.…”
mentioning
confidence: 99%
“…We are seeing more trials exclusively designed to answer questions of importance to older adults. The Edoxaban Low-Dose for Elder Care Atrial Fibrillation Patients (ELDERCARE-AF) trial tested a very low dose of edoxaban (15 mg), a quarter of the recommended starting dose, in an older Japanese population with frailty characterized by low body weight (≤45 kg), very low creatinine clearance (<30 mL/min), history of bleeding, or medication use that increased the risk of bleeding . They randomized 984 patients with AF older than 80 years who were considered to be inappropriate candidates for standard-dose anticoagulation for stroke prevention to very low-dose edoxaban or placebo, which was feasible because no anticoagulation was the default in this group.…”
mentioning
confidence: 99%
“…The trade-offs are best informed by considering both absolute rates of stroke or systemic embolism (15 vs 44 events) and major bleeding (20 vs 11 events) with edoxaban or placebo, respectively. The article by Kuroda et al in this issue of JAMA Cardiology presents a prespecified age subgroup analysis of the ELDERCARE-AF trial across 3 age groups (80-84, 85-89, ≥90 years). As expected, event rates for bleeding and stroke increased with age; however, the main findings from the ELDERCARE-AF trial held in each subgroup, including among 127 nonagenarians.…”
mentioning
confidence: 99%
See 1 more Smart Citation